Zora and me : the cursed ground - Simon, T. R. (Tanya R.) (Candlewick Press, 2020)
Carrie and her best friend, Zora, discover that their town's resident mute can actually speak after all. Thinking they have discovered a great secret, the girls soon find out Mr. Polk's voluntary silence is part of a mysterious puzzle that goes back fifty years to the tragic story of Lucia, a slave girl.